"New photoluminescent polyethylene films grafted with a fluorescein derivative using gamma radiation". (May 2022) - Rojas-Montoya, Sandra M.; Vonlanthen, Mireille; Martínez-Serrano, Ricardo D.; Cuétara-Guadarrama, Fabián; Burillo, Guillermina; Rivera, Ernesto
Abstract: Fluorescein containing polymers were prepared from commercial polyethylene (PE) films by gamma radiation grafting. Direct irradiation method was used to graft acryloyl chloride (AC) groups on the PE film. Absorbed doses of 2, 4, 6 and 8 kGy were employed to obtain a series of polymers with different amounts of grafted AC groups. In a subsequent step, the desired polymers were obtained by esterification of the precursor grafted PE films with a fluorescein derivative bearing a tetraethylene glycol side chain. The gamma radiation grafting procedure requires small amounts of the fluorescein derivative and avoids the addition of radical initiators which are difficult to eliminate. The crystallinity, transparency as well as the mechanical properties of the pristine PE films were preserved. The obtained grafted PE films presented the characteristic fluorescein absorption and emission bands in the visible region of the UV–vis spectra. The obtained PE films will be studied for potential applications in color filtering and optical materials. Graphical abstract: Image 1 Highlights: Gamma radiation grafting was used to incorporate fluorescein derivative on PE films. Absorption and emission properties of fluorescein are preserved after grafting. The polymer films showed the excellent photoluminescent properties of fluorescein.